Fuzzy set theory - Khan, Imran Moez; Htike@Muhammad Yusof, Zaw Zaw; Khalifa, Othman Omran (IIUM Press, 2011)
Fuzzy set theory was introduced in 1965 by Dr. Lotfi Zadeh to represent/manipulate data and information possessing nonstatistical uncertainties. He has developed considerably since its inception. Although initially the new and revolutionary ideas were viewed controversially in the realm of mathematics, they were more welcomed in several fields of engineering, especially control engineering, as they provided a good interface with real world applications of mathematics. The main advantage of fuzzy mathematics is that practical situations can be represented in more than one condition and mathematically rigorous calculations can be performed without the need to restrict the problem in only one representation. One automatic consequence of this is that fuzzy mathematics allows for much more realistic models of real-world situations - a need keenly felt in intelligent video surveillance